The effects of firm-initiated clawback provisions on earnings quality and auditor behavior - Chan, Lilian H.; Chen, Kevin C.W.; Chen, Tai-Yuan; Yu, Yangxin (Journal of Accounting and Economics, 2012)
While firm-initiated compensation recovery (or clawback) provisions are gaining popularity and the recently enacted Dodd-Frank Act seeks to make the clawback of erroneously awarded compensation mandatory for all listed companies, little is known about their effectiveness. We find that the incidence of accounting restatements declines after firms initiate such provisions. In addition, we show that investors and auditors view such provisions as associated with increased accounting quality and lower audit risk. Specifically, we find that firms' earnings response coefficients increase after the adoption of clawback provisions. Further, for firms that adopt clawbacks, auditors are less likely to report material internal control weaknesses, charge lower audit fees, and issue audit reports with a shorter lag.